Safety Issue of Changed Nanotoxicity of Zinc Oxide Nanoparticles in the Multicomponent System. (1st August 2019) - Huang, Yanan; Ding, Lin; Li, Chenchen; Wu, Min; Wang, Mimi; Yao, Chenjie; Yin, Xuelian; Zhang, Junfeng; Liu, Jinliang; Zhang, Yong; Wu, Minghong; Wang, Yanli
Abstract: When nanomaterials are exposed to complex systems, such as food, they may cause significant changes in physical and chemical properties and even toxicity. The toxicity evaluation of complex systems is urgent. Unfortunately, so far, there is no database established about the toxicity changes of nanoparticles in composite systems. In this paper, the changes and toxicity mechanism of zinc oxide nanoparticles (ZnO NPs) in a composite system are studied. The results show that the dissolution of zinc ions (Zn 2+ ) in acidic systems (vitamin C, tartaric acid, or citric acid) increases the toxicity of ZnO NPs. However, the toxicity of ZnO NPs is reduced by the complexation effect with Zn 2+ in phosphoric acid, phosphate, and glutathione systems. The influence of titanium dioxide nanoparticles (TiO2 NPs) on the toxicity of ZnO NPs depends on size and surface properties. In brief, the intracellular Zn 2+ homeostasis level is the decisive factor in determining the toxicity change in complex systems. The results indicate that the toxicity changes are very different in combined systems, which may have potential food safety issues, especially for unstable nanoparticles. Abstract : The toxicity of ZnO nanoparticles (NPs) changes in different systems with different mechanisms. The dissolution of ZnO NPs and the amount of free Zn 2+ inside cells play an important role in the toxicity of ZnO NPs. In brief, the intracellular Zn 2+ homeostasis level is the decisive factor in determining the toxicity change in complex systems.